2010
DOI: 10.1017/s0043933910000097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of incubation temperature on hatching and carcass performance of broilers

Abstract: In the past 20 years, broiler production has increased in hot climate countries, due to a greater potential for further growth. Thus, there is a necessity to improve thermotolerance of broilers produced in hot climates. Incubation period will become increasingly important in enhancing thermotolerance, because higher temperatures during incubation may lead to an elevation of the thermoregulatory set-point after hatch. Two recent experiments, conducted to determine the effect of high incubation temperature (INC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…On the other hand, Christina et al (2007) found that high incubation temperatures increase chick initial body weight. In contrast to our findings, Yalcin et al (2010) reported that chick weights are not influenced by incubation temperature. The results of the present study generally agree with various studies reporting that incubation temperatures influence broiler performance (Shafey, 2004;Lourens et al, 2005Lourens et al, , 2007Meijerhof, 2009a).…”
Section: The Effects Of Different Eggshell Temperatures Between Embrycontrasting
confidence: 99%
“…On the other hand, Christina et al (2007) found that high incubation temperatures increase chick initial body weight. In contrast to our findings, Yalcin et al (2010) reported that chick weights are not influenced by incubation temperature. The results of the present study generally agree with various studies reporting that incubation temperatures influence broiler performance (Shafey, 2004;Lourens et al, 2005Lourens et al, , 2007Meijerhof, 2009a).…”
Section: The Effects Of Different Eggshell Temperatures Between Embrycontrasting
confidence: 99%
“…This result was consistent with the results of both long-term hightemperature, environment-treated studies (Piestun et al, 2008;Akşit et al, 2010;Yalçin et al, 2010) and short-term high-temperature, environment-treated studies (Moraes et al, 2004;Yahav et al, 2004a and2004b;Collin et al, 2007). By contrast, there are few studies suggesting that the high temperature applied during incubation has an effect on the hatching weight in broilers.…”
Section: Discussionsupporting
confidence: 89%
“…Several previous studies had been interested with the effects of dietary protein on carcass traits of broilers (Rezaei et al, 2004;Sterling et al, 2006;and Yalcin et al, 2010) and some reports-in agreement with the present study-failed to detect significant change in dressing % (Berri et al., 2008), abdominal fat (Kobayashi et al, 2013; and Guardia et al, 2014), breast meat yield % (Guardia et al, 2014) or thigh yield % (Berri et al, 2008). Nonsignificant effect of protease supplementation to low protein broiler diets which recorded in the current study confirmed the results of Freitas et al (2011) who reported insignificant effect of adding graded levels (from 100 ppm to 1600 ppm) of protease (75000 U/g) to low protein (1%) and low energy (up to 150 kcal/kg diet) diet on % of carcass yield, abdominal fat, breast meat, thigh and drumsticks.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between dietary protein and carcass characteristics have been studied by many researchers. Some of them concluded the response of carcass yield to dietary crude protein (Rezaei et al, 2004;and Sterling, et al, 2006), while other researchers reported an effect of dietary protein on either chemical or physical characteristics of chicken meat (Furlan et al, 2004;Berri, et al, 2008;and Yalcin et al, 2010). On the other side, some researchers failed to detect any significant difference in quantitative or qualitative broiler carcass characteristics as a response of varying dietary protein level or amino acids profile (Jamroz et al, 1981;Jamroz et al, 1984;Daszkiewicz et al, 1998;Gardzielewska et al, 2005;and Guardia, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%